Occupational safety and health practice: a study at rubber manufacturing industry by using hirarc - Ramli, Mohamad Najmi; Ahmad Jais, Mohamad Harizat; Khalid, Amir; Jaat, Norrizam; Manshoor, Bukhari; Noranai, Zamri (Penerbit UTHM, 2020)
Occupational Safety and Health Act (OSHA) is a discipline with broad scope involving many specialized fields. The definition of safety is the state of being ‘safe’, condition of being protected against physical, social, spiritual, financial, political, emotional, occupational, psychological, educational or other types of consequences of failure, damage, error, accidents, harm or any other events which can be considered non-desirable. Health is a state of complete physical, mental, and social well-being and not merely the absence of disease and infirmity. Engineers play their roles at workstations to ensure the safety and health of each staff is in good conditions with proper ergonomic condition. This study conducted occupational safety and health act study at Kenny Leather (M) Sdn Bhd. The site visit, observation and interview session were conducted. The objective of this study is to identify the current or potential hazard that might be occurred in the factory. This study also providing the suitable solution and precaution step towards the zero hazard for the factory for reducing the possible accidents or injuries. Some of the suggestion that has collected through data collected was carried out through site visit using Preliminary Hazard Analysis (PHA) and HIRARC form by interviewing several workers. As a result, this study gave recommendations to the company in order to practice the safe and no harm work practice and gives priority to the safety first.